Symposium: Understanding the Connections Among Creativity, Spirituality and Wholeness, and their Significance for Teaching, Learning and Living - Kumar, Ashwani; Irwin, Rita L.; Kelly, Vicki; Sameshima, Pauline; Snowber, Celeste (Journal of the Canadian Association for Curriculum Studies, 2020)
This symposium will initiate an inquiry into the relationship that exists, can exist and should exist between creativity and spirituality, and the significance of looking at creativity and spirituality from holistic perspectives. The panelists will explore these relationships in light of their own scholarly research and artistic and teaching practices, and they will underscore the significance of understanding these relationships for teaching, learning and living. The key questions that the panelists will explore in this symposium include the following: • How are creativity, spirituality and wholeness connected? • What is the significance of exploring and understanding these notions in relation to each other? For instance, how does seeing creativity as linked with spirituality and wholeness result in a more fulsome understanding of creativity? • How might understanding the interconnections between creativity, spirituality and wholeness impact how we teach, learn and live? • How may we introduce ourselves and our students to the inter-relatedness of creativity, spirituality and a notion of wholeness? Why is doing so important?